An examination of small heat shock protein gene expression in Xenopus laevis embryos and A6 kidney epithelial cells - Ohan, Nicholas (University of Waterloo, 1997)
In this study, using Northern blot analysis, the presence of very low levels of hsp30 messenger RNA was detected in late blastula stage Xenopus laevis embryos exposed to heat shock. The relative levels of these pre-tailbud (PTB) hsp30 mRNAs increased at the gastrula and neurula stage followed by a dramatic enhancement in heat-shocked tailbud and tadpole stage embryos (20- to 40-fold relative to late blastula). Interestingly, treatment of blastula or gastrula embryos at a temperature of 37*C for 1 h, or with cycloheximide, a protein synthesis inhibitor, followed by heat shock led to enhanced accumulation of the pre-tailbud (PTB) hsp30 mRNAs. Hsp70, hsp87, and actin messages were not stabilized at high temperatures or by cycloheximide treatment. Finally, hsp30D mRNA, which has been previously shown to be first heat-inducible at the mid-tailbud stage using RT-PCR analysis, was not detected by RT-PCR analysis of cycloheximide-treated, heat-shocked blastula stage embryos confirming that it is not a member of the PTB hsp30 mRNAs. This indicates that differential gene expression and mRNA stability are involved in the regulation of hsp30 gene expression during early Xenopus laevis development.
Keywords: Harvested from Collections Canada